2011
DOI: 10.1590/s0100-06832011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock and its compartments in a subtropical oxisol under long-term tillage and crop rotation systems

Abstract: Soil organic matter (SOM) plays a crucial role in soil quality and can act as an atmospheric C-CO 2 sink under conservationist management systems. This study aimed to evaluate the long-term effects (19 years) of tillage (CT-conventional tillage and NT-no tillage) and crop rotations (R0-monoculture system, R1-winter crop rotation, and R2-intensive crop rotation) on total, particulate and mineralassociated organic carbon (C) stocks of an originally degraded Red Oxisol in Cruz Alta, RS, Southern Brazil. The clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
9
43
0
4
Order By: Relevance
“…In southern Brazil, a recent study carried out by Ferreira [45] in six different croplands showed that there was an average SOM decline of 23% in the 0-100 cm soil layer after 25 years of CT. On-farm research showed SOM values that were similar to those observed in the few long-term experiments carried out in Rio Grande do Sul [44]. On the other side, restoration of SOM with NT in southern Brazil has been shown to be a long term process (>20 years) with increases ranging from 61%-117% ( Figure 7) depending upon climate, clay content and crop rotation.…”
Section: Developing Cropping Systems For Sustained Grain Yield Maintsupporting
confidence: 74%
See 2 more Smart Citations
“…In southern Brazil, a recent study carried out by Ferreira [45] in six different croplands showed that there was an average SOM decline of 23% in the 0-100 cm soil layer after 25 years of CT. On-farm research showed SOM values that were similar to those observed in the few long-term experiments carried out in Rio Grande do Sul [44]. On the other side, restoration of SOM with NT in southern Brazil has been shown to be a long term process (>20 years) with increases ranging from 61%-117% ( Figure 7) depending upon climate, clay content and crop rotation.…”
Section: Developing Cropping Systems For Sustained Grain Yield Maintsupporting
confidence: 74%
“…Campos et al [44] in a long-term experiment carried out on an Oxisol reported a linear relationship between crop residue input and SOC stock in the 0-30 cm soil depth ( Figure 9). This study supports previous research suggesting an annual dry matter input of 8-10 Mg·ha…”
Section: Developing Cropping Systems For Sustained Grain Yield Maintmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have shown that most of the C accumulated in minimal tillage and no-till systems, relative to CT, is stored in the mineral-associated fraction, emphasizing the importance of the organomineral interaction as a stabilization mechanism in these systems (CAMPOS et al, 2011;PINHEIRO et al, 2015). In contrast, soil organic C associated with sand fractions was the most sensitive C fraction responding to soil tillage systems in a short period of time in areas cultivated with sugarcane in Australia (THORBURN et al, 2012) and with a rotation of vegetables, including tomato, green pepper and beans, in Rio de Janeiro State, Brazil (PINHEIRO et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure may be applied to evaluate the dynamics of the total organic carbon (TOC), even for short-term changes. Particulate organic matter is closely related to the crop residue added to the soil surface and is sensitive to changes in management, and the fraction associated with minerals typically represents most of the soil C ( BLANCO-MOURE et al, 2013;CAMPOS et al, 2011). Chemical fractionation separates the material into humic acids, fulvic acids, and humin.…”
Section: Introductionmentioning
confidence: 99%